PEMBELAJARAN MUSIK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK KELAS XI - Ridwan Setia Putra (Jurnal Penelitian Musik, 2022)
The aim of this study is to create a music lesson plan using a project-based learning model. The research methodology used in this study is qualitative study with a descriptive approach. The data collection procedure used in this research is documentary research. The data analysis procedure used in this study are stages of data reduction, data presentation, and verification. The results of the study is the researcher made lesson plans for 7 (seven) meetings, each meeting has a duration of 90 minutes (2 hours of lessons x 45 minutes). In the compiled lesson plans, which the researcher has made, contain 3 (three) steps of learning activities, namely preliminary activities, main activities and closing activities.